A systematic literature review of patient self-assessment instruments concerning quality of primary care in multiprofessional clinics. (1st March 2022) - Derriennic, Jérémy; Nabbe, Patrice; Barais, Marie; Le Goff, Delphine; Pourtau, Thomas; Penpennic, Benjamin; Le Reste, Jean-Yves
Abstract: Background: Quality of care remains a priority issue and is correlated with patient experience. Measuring multidimensional patient primary care experiences in multiprofessional clinics requires a robust instrument. Although many exist, little is known about their quality. Objective: To identify patient perception instruments in multiprofessional primary care and evaluate their quality. Methods: Systematic review using Medline, Pascal, PsycINFO, Google Scholar, Cochrane, Scopus, and CAIRN. Eligible articles developed, evaluated, or validated 1 or more self-assessment instruments. The instruments had to measure primary care delivery, patient primary care experiences and assess at least 3 quality-of-care dimensions. The COnsensus-based Standards for the selection of health status Measurement Instruments (COSMIN) checklist was used to assess methodological quality of included studies. Instrument measurement properties were appraised using 3 possible quality scores. Data were combined to provide best-evidence synthesis based on the number of studies, their methodological quality, measurement property appraisal, and result consistency. Subscales used to capture patient primary care experiences were extracted and grouped into the 9 Institute of Medicine dimensions. Results: Twenty-nine articles were found. The included instruments captured many subscales illustrating the diverse conceptualization of patient primary care experiences. No included instrument demonstrated adequate validity and the lack of scientific methodology for assessing reliability made interpreting validity questionable. No study evaluated instrument responsiveness. Conclusion: Numerous patient self-assessment instruments were identified capturing a wide range of patient experiences, but their measurement properties were weak. Research is required to develop and validate a generic instrument for assessing quality of multiprofessional primary care. Trial registration: Not applicable. Lay Summary: Good quality health care should be safe, effective, timely, efficient, equitable, and patient-centred. Patients describing their health care experience provides information about the quality of health care. Patient health care experiences can be recorded using questionnaires. These questionnaires measure specific aspects of the health care experience such as communication and timeliness, as well as their experience within a multiprofessional clinic, where different health professionals work together. These specific measurements evaluate how health care affects the patient's experience. However, more information is needed to understand which questionnaires are the most appropriate to evaluate patient experience. The objective of this systematic review study is to identify the number of patient experience questionnaires available and evaluate their effectiveness. Researchers examined different literature databases to identify questionnaires which measure primary care delivery, patient primary care experiences and assess at least 3 aspects of quality of care. Twenty-nine questionnaires were found which measured a wide range of patient experiences but none of them were found to be sufficient to understand all aspects of patient experience. An effective questionnaire needs to be developed and validated to assess quality of primary care in multiprofessional practices.